Impact of Different Measures of Body Size on the Radiation Dose During Coronary Angiography and Percutaneous Coronary Intervention: Results from a Large Single Center Cohort. (May 2022) - Verdoia, Monica; Pipan, Pierpaolo; Viola, Orazio; Francesca Brancati, Marta; La Cognata, Sara; Novara, Francesca; Bristot, Filippo; D'Amico, Giuseppina; Ravetto, Cinzia; Fusco, Massimo; Giachino, Paolo; Tonella, Manuela; et al.
Efforts to reduce and optimize the radiation exposure during coronary angiography and intervention have pointed at patients' body size as a major determinant of irradiation for the patients and operators. We aimed at comparing body weight and body mass index (BMI) among consecutive patients undergoing angiographic procedures (coronary angiography and/or interventions) in a single center. Patients were divided in normal weight (NW, BMI <25 Kg/m 2 ) and overweight (OW, BMI ≥25 Kg/m 2 ). Patients' dose exposure was evaluated as dose area product (DAP), time of exposure (fluoroscopy duration), and relative DAP (DAP/minutes of exposure). We included 748 patients, 61.6% undergoing percutaneous coronary interventions and 56.8% classified as OW. OW patients were more often men ( P < .001), with history of hypertension ( P < .001) and diabetes ( P = .001). Mean DAP and relative DAP were significantly higher among OW compared with NW patients ( P < .001). DAP and relative DAP were directly related with body weight (both r = .22, P < .001); a similar linear association was also described for BMI (r = .18, P < .001 and r = .19, P < .001, respectively). At multivariate analysis, however, body weight, but not BMI, independently predicted the DAP. Therefore, body weight should be considered as the preferred indicator of body size in the setting and optimization of radiation exposure during coronary diagnostic and intervention procedures.